Analysis of Factors Influencing Laboratory Turnaround Time (TAT) at Grandmed Hospital Lubuk Pakam - Dian Hastari Ningrum; Barita Aritonang; Sa'adah Siregar (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Turnaround Time (TAT) is an important indicator of laboratory service quality that supports accurate diagnosis and clinical decision-making. Delays in laboratory results may be influenced by pre-analytical, analytical, and post-analytical phases. This study aimed to analyze the factors influencing laboratory Turnaround Time (TAT) at Grandmed Hospital Lubuk Pakam. This study used a quantitative approach with an analytical observational design and a cross-sectional method. The population consisted of 32 clinical laboratory personnel selected using total sampling. Data were collected through validated and reliable questionnaires and secondary data from laboratory information system records. Data were analyzed using univariate and bivariate analysis with Spearman’s rank correlation test at a 95% confidence level. The results showed that most TAT values met the standard (87.5%). The average TAT for emergency services was 87 minutes, outpatient services 118 minutes, and inpatient services 130 minutes, all within the minimum service standard (≤140 minutes). Pre-analytical factors (r = 0.604; p = 0.000) and analytical factors (r = 0.545; p = 0.001) had significant effects on TAT, while post-analytical factors were not significant (r = -0.098; p = 0.595). In conclusion, pre-analytical and analytical factors are the main determinants of TAT, indicating the need to improve these stages to enhance laboratory service quality.